2021
DOI: 10.3390/horticulturae7020016
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Si and SiNPs in Improving Thermotolerance of Wheat Photosynthetic Machinery via Upregulation of PsbH, PsbB and PsbD Genes Encoding PSII Core Proteins

Abstract: Photosystem II is extremely susceptible to environmental alterations, particularly high temperatures. The maintenance of an efficient photosynthetic system under stress conditions is one of the main issues for plants to attain their required energy. Nowadays, searching for stress alleviators is the main goal for maintaining photosynthetic system productivity and, thereby, crop yield under global climate change. Potassium silicate (K2SiO3, 1.5 mM) and silicon dioxide nanoparticles (SiO2NPs, 1.66 mM) were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…In the present study, the qRT-PCR analysis revealed that heat stress downregulated the expression of the psbA and psbB genes, which were linked to PS II inactivation. Reduced photosynthetic pigments and organic solutes, such as soluble sugars, sucrose, and proline, were associated with the deleterious consequences of HS stress [ 131 ]. Salt stress was reported to cause the degradation of D1 protein (encoded by the psbA gene) in Avena sativa plants, as well as the downregulation of psbA , psbB , psbC , and psbD [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the qRT-PCR analysis revealed that heat stress downregulated the expression of the psbA and psbB genes, which were linked to PS II inactivation. Reduced photosynthetic pigments and organic solutes, such as soluble sugars, sucrose, and proline, were associated with the deleterious consequences of HS stress [ 131 ]. Salt stress was reported to cause the degradation of D1 protein (encoded by the psbA gene) in Avena sativa plants, as well as the downregulation of psbA , psbB , psbC , and psbD [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that Si participates in the regulation and accumulation of soluble sugars and carbohydrates, which are an important factor for the quality of the fruits, since they determine the flavor (Peris-Felipo et al, 2020). In addition, these compounds serve as osmoprotectors, carbon sources and free radical scavengers in plants (Hassan et al, 2021). Zhu et al (2016) showed that the application of 0.3 mM Na 2 SiO 3 in the nutrient solution increased the content of soluble sugars (glucose, sucrose and fructose) in cucumber plants.…”
Section: Discussionmentioning
confidence: 99%
“…The complex of proteins and pigments known as photosystem II is crucial for the reduction of plastoquinone, oxygen evolution, and water splitting. Compared to PS I in chloroplasts, PS II is more sensitive to abiotic stress 4 , 42 , 43 . It has been demonstrated that chlorophyll fluorescence characteristics such as the efficiency of PSII, can accurately indicate the level of stress in plants 44 .…”
Section: Discussionmentioning
confidence: 99%